2008
DOI: 10.1093/europace/eun325
|View full text |Cite
|
Sign up to set email alerts
|

Implantable cardioverter defibrillators and Chagas' disease: results of the ICD Registry Latin America

Abstract: This registry confirms that ICD therapy provides protection by effectively terminating life-threatening arrhythmias in patients with Chagas' disease. This is especially so when patients receive the device for secondary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 19 publications
1
31
0
16
Order By: Relevance
“…Myocardial fi brosis and areas of slow electrical conduction result in mechanical alterations in both timing and function. With the development of therapeutic strategies to prevent death from ventricular fi brillation, particularly the use of implantable cardioverter-defi brillators (ICDs), accurate patient stratifi cation based on the future risk of arrhythmic events has become very relevant in ChD (3) .…”
Section: Of Great Frequency Are Also the Sudden Deaths In The Cardiacmentioning
confidence: 99%
“…Myocardial fi brosis and areas of slow electrical conduction result in mechanical alterations in both timing and function. With the development of therapeutic strategies to prevent death from ventricular fi brillation, particularly the use of implantable cardioverter-defi brillators (ICDs), accurate patient stratifi cation based on the future risk of arrhythmic events has become very relevant in ChD (3) .…”
Section: Of Great Frequency Are Also the Sudden Deaths In The Cardiacmentioning
confidence: 99%
“…4,5 Patients also require palliative care for the cardiomyopathy, ranging from drug therapy to pacemakers and cardiac transplants. 6 Thus treatment can cost up to over 1,000 USD per year and per patient. 7 Prevention currently only relies on vector control, which has considerably reduced disease incidence and prevalence in most Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Muratore et al (50), (51) and Fonseca et al (53) found no difference between the populations with and without Chagas disease in the numbers of arrhythmia episodes, shocks, and deaths. In contrast, the studies by Martinelli-Filho et al (44) , Rabinovich et al (51) , Moreira (49) , Cardinalli-Neto et al (54) , Cardinalli-Neto et al (55) , Barbosa et al (52) and the ICD registry for patients with Chagas disease in Latin America, published in 2009 (56) , found differences between the chagasic and non-chagasic populations. ChD groups had higher numbers of ventricular arrhythmias, a higher percentage of patients receiving appropriate therapy and increased numbers of shocks overall.…”
Section: Implantable Cardioverter Defi Brillatormentioning
confidence: 92%
“…The groups did not differ in the outcomes for mortality and the number of inappropriate shocks. Mortality predictors for Chagas disease patients with ICDs were the following: the number of shocks per patient (56) , age ≥ 65 years 57 and LVEF ≤ 30% (57) . Martinelli et al (58) investigated 116 consecutive ChD patients with ICDs implanted for the secondary prevention of arrhythmias; 50% of the cohort received appropriate shock therapy.…”
Section: Implantable Cardioverter Defi Brillatormentioning
confidence: 99%